2013
DOI: 10.5770/cgj.16.64
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Older Adults Hospitalized with a Diagnosis of Failure to Thrive

Abstract: Backgroundolder adults are sometimes hospitalized with the admission diagnosis of failure to thrive (FTT), often because they are not felt safe to be discharged back to their current living arrangement. It is unclear if this diagnosis indicates primarily a social admission or suggests an acute medical deterioration. The objective of this study was to explore the level of acuity and medical investigations commonly conducted among older hospitalized adults with a diagnosis of FTT.MethodsWe conducted a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Studies have also suggested that labels are powerful in the healthcare setting and may alter how patients are perceived [6,11]. An earlier retrospective cohort study hypothesized that acute medical illness rather than social factors is the primary reason for admission for patients labeled as FTT, as the majority of patients in this study received an extensive medical workup and interventions such as intravenous fluids and antibiotics [12].…”
Section: Introductionmentioning
confidence: 92%
“…Studies have also suggested that labels are powerful in the healthcare setting and may alter how patients are perceived [6,11]. An earlier retrospective cohort study hypothesized that acute medical illness rather than social factors is the primary reason for admission for patients labeled as FTT, as the majority of patients in this study received an extensive medical workup and interventions such as intravenous fluids and antibiotics [12].…”
Section: Introductionmentioning
confidence: 92%
“…Diseasefocused specialists who push on with the only course they know sometimes decry their frail patients as being unsuitable or requiring social support or failing to cope or thrive. 3 Many hospitals-and practitionersstill somehow expect patients to present with primary complaints that give rise to well defined problems, which they can manage successfully using pathways that can be audited, such as time to thrombolytic event in an acute stroke or myocardial infarction.…”
Section: What Proportion Of Older Adults In Hospital Are Frail?mentioning
confidence: 99%
“…Data published in February, 2018, by the European Centre for Disease Prevention and Control 3 have shown that measles cases in Europe trebled in 2017, with large outbreaks ongoing in several countries due to suboptimal vaccination coverage, but also linked to cross-border migration within the region of migrants moving to and from large epidemics. Yet, a lack of clarity remains on what vaccinations should be given or readministered to migrants on arrival and what costeffective approaches will improve coverage.…”
Section: What Proportion Of Older Adults In Hospital Are Frail?mentioning
confidence: 99%
“…Patient hospitalization represents a potentially stressful period in a patient's disease trajectory. It often represents a complication of a patient's disease or treatment that requires specialized care and may be a marker of when a caregiver's ability to care for the patient at home is exceeded . Better characterization of caregivers of older adults with cancer and the impact caregiving has on them has important implications on patient care, especially at discharge, and is crucial to understand and address the needs of this growing population of caregivers …”
mentioning
confidence: 99%
“…It often represents a complication of a patient's disease or treatment that requires specialized care and may be a marker of when a caregiver's ability to care for the patient at home is exceeded. 10 Better characterization of caregivers of older adults with cancer and the impact caregiving has on them has important implications on patient care, especially at discharge, and is crucial to understand and address the needs of this growing population of caregivers. 11,12 The objectives of this study were to characterize informal caregivers of older adults with cancer admitted to the hospital, determine caregiver QOL, and identify factors associated with poorer caregiver QOL.…”
mentioning
confidence: 99%